Sustainable collaborative innovation capability enhancement paths of marine ranching: Supernetwork analysis perspective. (1st January 2023) - Wan, Xiaole; Li, Qianqian; Zhang, Guixian; Zhang, Kuncheng; Wang, Zhiwen
Abstract: In order to solve the problem of weak innovation ability of marine ranching enterprises, it is necessary to establish a collaborative innovation system involving multiple subjects to break the innovation boundary of enterprises. At the same time, because the collaborative innovation system of marine ranching is a complex network system, this paper designs the supernetwork model of collaborative innovation in marine ranching based on supernetwork theory, by analyzing the operation mechanism of relationship coordination network, resource sharing network and cooperative innovation network in supernetwork, solving the network equilibrium conditions and the path to realize supernetwork equilibrium based on variational inequality. Through numerical examples, this paper draws the following conclusions: (a) When the relationship coordination network, resource sharing network and cooperative innovation network all reach equilibrium, the marginal total cost of the three networks is equal to the marginal total value, the cooperative innovation super network of marine ranching reaches equilibrium state; (b) the supernetwork model of collaborative innovation in marine ranching needs to go through two states: "initial-intermediate" and "intermediate-equilibrium" to achieve equilibrium. Finally, this paper puts forward suggestions on the behavior of the participants to ensure the stable operation of the marine ranching collaborative innovation system.